2010
DOI: 10.1111/j.1365-2966.2010.17920.x
|View full text |Cite
|
Sign up to set email alerts
|

Escape fraction of ionizing photons from high-redshift galaxies in cosmological SPH simulations

Abstract: Combing the three‐dimensional radiative transfer (RT) calculation and cosmological smoothed particle hydrodynamics (SPH) simulations, we study the escape fraction of ionizing photons (fesc) of high‐redshift galaxies at z= 3–6. Our simulations cover the halo mass range of Mh= 109–1012 M⊙. We post‐process several hundred simulated galaxies with the Authentic Radiative Transfer (art) code to study the halo mass dependence of fesc. In this paper, we restrict ourselves to the transfer of stellar radiation from loca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
236
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(279 citation statements)
references
References 60 publications
37
236
6
Order By: Relevance
“…More recently, using a high-resolution cosmological zoom-in simulation of galaxy formation, Ma et al (2015) found a considerably lower (< 5%; much less than required by reionization models) and a non-evolving escape fraction. This unchanging trend of fesc is as well consistent with many other earlier results (Gnedin 2008;Yajima et al 2011). A decreasing tendency of escape fraction with redshift has also been reported in the literature (Wood & Loeb 2000;Kimm & Cen 2014).…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…More recently, using a high-resolution cosmological zoom-in simulation of galaxy formation, Ma et al (2015) found a considerably lower (< 5%; much less than required by reionization models) and a non-evolving escape fraction. This unchanging trend of fesc is as well consistent with many other earlier results (Gnedin 2008;Yajima et al 2011). A decreasing tendency of escape fraction with redshift has also been reported in the literature (Wood & Loeb 2000;Kimm & Cen 2014).…”
Section: Introductionsupporting
confidence: 80%
“…• From the match between the observed high-redshift LFs and our model predictions, we find that the best-fit values for both ǫ * and fesc remains somewhat constant with redshifts: ǫ * at ∼ 4% and fesc ∼ 10% for z = 6 − 9 (Gnedin 2008;Yajima et al 2011;Ma et al 2015). We have also obtained the tightest constraint available to our knowledge on on fesc (> 10%) at z = 10.…”
Section: Discussionmentioning
confidence: 50%
“…Finally, we have made the simplifying assumption of using a mass-independent f esc at all z. This is partly motivated by the uncertainty regarding the mass-dependence of f esc : while some authors find f esc to decrease with an increase in the halo mass (Razoumov & Sommer-Larsen 2010;Yajima et al 2011;Ferrara & Loeb 2013) …”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…However, the value of f esc for an individual galaxy is strongly dependent on its chemical, structural, and kinematic properties, and there exists considerable theoretical and observational evidence to suggest that the average f esc does indeed vary with redshift, mass, and/or star formation rate (e.g. Gnedin et al 2008;Wise & Cen 2009;Paardekooper et al 2011;Yajima et al 2011;Kuhlen & Faucher-Giguère 2012;Mitra et al 2013;Paardekooper et al 2015). …”
Section: An Evolving Escape Fractionmentioning
confidence: 99%